2001
DOI: 10.1073/pnas.071043698
|View full text |Cite
|
Sign up to set email alerts
|

ClpA mediates directional translocation of substrate proteins into the ClpP protease

Abstract: The intracellular degradation of many proteins is mediated in an ATP-dependent manner by large assemblies comprising a chaperone ring complex associated coaxially with a proteolytic cylinder, e.g., ClpAP, ClpXP, and HslUV in prokaryotes, and the 26S proteasome in eukaryotes. Recent studies of the chaperone ClpA indicate that it mediates ATP-dependent unfolding of substrate proteins and directs their ATP-dependent translocation into the ClpP protease. Because the axial passageway into the proteolytic chamber is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
123
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(129 citation statements)
references
References 33 publications
(41 reference statements)
6
123
0
Order By: Relevance
“…This architecture imposes an obligatory directionality to protein translocation that would proceed, in the case of ClpA, from AAAϩ module 1 to AAAϩ module 2 that contains the GYVG motif (14). Assuming that this directionality is a conserved feature of the Hsp100 common mechanism, aggregated substrates would be initially encountered by AAAϩ module 1 of Hsp104 and extruded from the hexamer through an exit pore in AAAϩ module 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This architecture imposes an obligatory directionality to protein translocation that would proceed, in the case of ClpA, from AAAϩ module 1 to AAAϩ module 2 that contains the GYVG motif (14). Assuming that this directionality is a conserved feature of the Hsp100 common mechanism, aggregated substrates would be initially encountered by AAAϩ module 1 of Hsp104 and extruded from the hexamer through an exit pore in AAAϩ module 2.…”
Section: Discussionmentioning
confidence: 99%
“…This proposed mechanism of action is different from that of other members of the Hsp100 family, including ClpA (5), ClpX (6,7), and HslU (8), which form complexes with oligomeric proteases and function to unfold proteins in an ATP-dependent manner for proteolysis. Biochemical and structural analyses (9 -12) indicate that, in these Hsp100s, ATP hydrolysis is coupled to global unfolding of substrates as they are threaded through an axial channel of the Hsp100 oligomer (11,13,14) and translocated into the chamber of the associated protease.…”
mentioning
confidence: 99%
“…ClpXP and ClpAP, have poor homology to proteasomes but share a similar architecture (39) consisting of a regulatory complex containing an ATPase hexamer that recognizes, unfolds, and transfers substrate proteins into a structurally distinct co-axially aligned catalytic chamber where proteolysis takes place (40). These bacterial proteases also initiate polypeptide proteolysis at the end bearing a recognition tag (5,37). We have shown that degradation tag and entry site co-localize in ODC, the first native labile protein characterized in this way.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike ClpB or its yeast Hsp104 homolog, most members of the HSP100͞Clp family associate with an oligomeric peptidase to form an ATP-dependent protease. For some HSP100͞Clp proteins, like ClpA and ClpX, it was shown that they act as chaperones by promoting the ATP-dependent unfolding (12) and translocation of substrate proteins into the catalytically active centers of the associated ClpP peptidase ring (13,14). However, these and other HSP100͞Clp proteins also have chaperone activities independent of their role in the protease complex (12,15,16).…”
mentioning
confidence: 99%